2020
DOI: 10.5194/tc-2020-185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basal traction mainly dictated by hard-bed physics over grounded regions of Greenland

Abstract: Abstract. On glaciers and ice sheets, identifying the relationship between velocity and traction is critical to constrain the bed physics that control ice flow. Yet in Greenland, these relationships remain unquantified. We determine the spatial relationship between velocity and traction in all eight drainage catchments of Greenland. The basal traction is estimated using three different methods over large grid cells to minimize interpretation biases associated with unconstrained rheologic parameters used in num… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
3
3
0
Order By: Relevance
“…Our findings are consistent with a recent study showing that the simple approach overestimates the basal stresses compared to the Full-Stokes solution 32 . In addition to the uncertainty imposed by the simplified stress-balance, other uncertainties include unknown temperatures of the basal shear layer and the uncertainties from velocity datasets (see methods for a detailed discussion of the uncertainties).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with a recent study showing that the simple approach overestimates the basal stresses compared to the Full-Stokes solution 32 . In addition to the uncertainty imposed by the simplified stress-balance, other uncertainties include unknown temperatures of the basal shear layer and the uncertainties from velocity datasets (see methods for a detailed discussion of the uncertainties).…”
Section: Resultssupporting
confidence: 93%
“…The reason for the large discrepancies is likely the inability of the simplified approach to capture the complex flow regime of the Northeast Greenland ice stream in the NE sector, and the topography of numerous small outlet glaciers in the NW sector. Our findings are consistent with a recent study showing that the simple approach overestimates the basal stresses compared to the Full-Stokes solution 32 . In addition to the uncertainty imposed by the simplified stress-balance, other uncertainties include unknown temperatures of the basal shear layer and the uncertainties from velocity datasets (see methods for a detailed discussion of the uncertainties).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, Arthern et al (2015) found that the basal stress in Antarctica, on average, roughly agrees with a uniform value of 100 kPa, however this can change locally by order of magnitudes. Spatially aggregating inversions with models of different complexity, Maier et al (2021) found that large areas under the Greenland ice sheet broadly agree with hard-bed physics. The other possibility to constrain the friction law is to use several inversions to study the temporal changes; however this can be done only where the changes are sufficiently large.…”
mentioning
confidence: 90%